Comparison of tea tree oil 5%, tea tree oil 10%, and nystatin inhibition zones against vaginal Candida isolates in pregnancy - Ervianti, Evy; Damayanti; Purnamasari, Indah; Astari, Linda; Prasetyo, Budi; Endraswari, Pepy D; Utomo, Budi; Fitriani, Endang Wahyu; Indramaya, Diah Mira; Listiawan, M Yulianto; Sigit Prakoeswa, Cita Rosita (Journal of infection in developing countries, 2023)
Introduction: Vulvovaginal candidiasis (VVC) in pregnancy frequently develops into recurrent infections. Clinical study suggests that conventional topical treatments for VVC are not always enough to eradicate Candida spp. from the vaginal microenvironment. This study aimed to evaluate the antifungal activity of tea tree oil (TTO) 5% and TTO 10% against Candida species causing VVC in pregnancy. Methodology: In vitro experimental study was conducted in the Mycology Laboratory at Dermatovenereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya. Eighteen isolates of Candida species were isolated from the vaginal thrush of 15 pregnant women diagnosed with VVC from March to May 2021. Antifungal susceptibility of TTO 5% and TTO 10% was evaluated by the disc diffusion method, with the inhibitory zone diameter as the main outcome. Results: The mean inhibitory zone diameter of TTO 5%, TTO 10%, and nystatin against all Candida spp. was 7.26 mm, 8.64 mm, and 25.57 mm, respectively (p < 0.001). The mean inhibitory zone diameter of TTO 5%, TTO 10%, and nystatin tend to be larger in C. albicans compared to the non-albicans, but the difference is not significant. Nystatin displayed the largest mean inhibitory zone diameters compared to TTO 5% and TTO 10% (p < 0.001) in all Candida species. Increased concentration from TTO 5% to TTO 10% resulted in a slight increment in the mean inhibitory zone diameters in all-Candida species (p = 0.001). Conclusions: Tea Tree Oil displayed antifungal activity against Candida species causing VVC in pregnancy. Further studies are required to investigate optimal TTO concentrations as a VVC treatment in pregnancy.